2023
DOI: 10.3390/ijms241612843
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana benthamiana Class 1 Reversibly Glycosylated Polypeptides Suppress Tobacco Mosaic Virus Infection

Kamila A. Kamarova,
Natalia M. Ershova,
Ekaterina V. Sheshukova
et al.

Abstract: Reversibly glycosylated polypeptides (RGPs) have been identified in many plant species and play an important role in cell wall formation, intercellular transport regulation, and plant–virus interactions. Most plants have several RGP genes with different expression patterns depending on the organ and developmental stage. Here, we report on four members of the RGP family in N. benthamiana. Based on a homology search, NbRGP1-3 and NbRGP5 were assigned to the class 1 and class 2 RGPs, respectively. We demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…To obtain a set of constructs encoding NbMIG21 fusions with various fluorescent proteins (35S-NbMIG21:GFP, 35S-NbMIG21:RFP, 35S-NbMIG21:YC, and NbMIG21:YN), a fragment encoding NbMIG21 without a stop codon and flanked by Acc65I/BamHI recognition sites was synthesized using the N-NbMIG21-Acc65I_f/N-NbMIG21-BamHI_r pair of primers. The NbMIG21 fragment was digested with Acc65I/BamHI and inserted into the pCambia-35S vector containing either a GFP-, RFP-, YN-, or YC-encoding sequence without a start codon [ 37 ], using the same sites. The NbMIG21 NoLSmut :GFP fragment was obtained as a product of overlap PCR, and mutations were inserted using NbMIG21-NoLS-mut_f and NbMIG21-NoLS-mut_r primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain a set of constructs encoding NbMIG21 fusions with various fluorescent proteins (35S-NbMIG21:GFP, 35S-NbMIG21:RFP, 35S-NbMIG21:YC, and NbMIG21:YN), a fragment encoding NbMIG21 without a stop codon and flanked by Acc65I/BamHI recognition sites was synthesized using the N-NbMIG21-Acc65I_f/N-NbMIG21-BamHI_r pair of primers. The NbMIG21 fragment was digested with Acc65I/BamHI and inserted into the pCambia-35S vector containing either a GFP-, RFP-, YN-, or YC-encoding sequence without a start codon [ 37 ], using the same sites. The NbMIG21 NoLSmut :GFP fragment was obtained as a product of overlap PCR, and mutations were inserted using NbMIG21-NoLS-mut_f and NbMIG21-NoLS-mut_r primers.…”
Section: Methodsmentioning
confidence: 99%
“…For NbCoil:YN and NbMIG21:YC pair, YFP fluorescence was distributed in multiple subnuclear structures that corresponded to Cajal bodies (Figure 8, right). An antiviral protein, N. benthamiana reversibly glycosylated polypeptide 1 (NbRGP1) [37], was used as a negative control for the BiFC assay. We concluded that NbMIG21p is distributed between the nucleolus and Cajal bodies.…”
Section: Nbmig21-encoded Protein Sequence Analysis and Intracellular ...mentioning
confidence: 99%
“…For NbCoil:YC and NbMIG21:YN pair YFP fluorescence was distributed in multiple subnuclear structures that correspond to Cajal bodies (Figure 5B). An antiviral protein, N. benthamiana reversibly glycosylated protein 1 (NbRGP1) [37], was used as a negative control for BiFC assay. We concluded that NbMIG21p is distributed between nucleolus and Cajal bodies.…”
Section: Nbmig21p Intracellular Localizationmentioning
confidence: 99%
“…To obtain a set of constructs encoding NbMIG21 fusions with various fluorescent protein: 35S-NbMIG21:GFP, 35S-NbMIG21:RFP, 35S-NbMIG21:YC and NbMIG21:YN, a fragment encoding NbMIG21 without a stop codon and flanked by Acc65I/BamHI recognition sites was synthesized using "N-NbMIG21-Acc65I_f"/"N-NbMIG21-BamHI_r" pair of primers. This fragment was digested with Acc65I/BamHI and inserted into pCambia-35S vector containing either GFP-, RFP-, YN-or YC-encoding sequence without start codon [37] using the same sites.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…Nucleic acid delivery into plant cells could be applied to searching for host resistance [32][33][34][35] or susceptibility factors [36][37][38]. Solving fundamental problems in the field of plant-pathogen interactions paves the way to the transfer of the developed technologies to the applied biotechnology for crop defense and improvement, especially using such instruments as RNAi [12].…”
Section: Introductionmentioning
confidence: 99%